Exploring key factors influencing blockchain adoption in e-government: pilot study - Falih, Raed; Abdullah, Salfarina; Jusoh, Yusmadi Y.; Abdullah, Rusli; Pa, Noraini C.; Kadhim, Dheyaa J.; Altawaiha, Iyad (Society of Visual Informatics, 2024)
E-government systems face numerous challenges, including trust, privacy, transparency, security, traceability, and service delays. Blockchain technology holds promise for revolutionizing these systems by addressing their long-standing vulnerabilities. Despite the acknowledged potential of blockchain in enhancing e-government systems via improved security and transparency, empirical research on the factors influencing its adoption within government remains scarce. This pilot study addresses this gap by constructing and validating a theoretical model and a corresponding questionnaire. The development of the model and questionnaire followed a four-step methodology. Initially, potential influencing factors were identified and collected. These factors were then filtered and categorized into four main groups: Technological Specific Factors (TSFs), Organizational Specific Factors (OSFs), Individual Specific Factors (ISFs), and Environmental Specific Factors (ESFs). The Analytic Hierarchy Process (AHP) was applied to rank these factors based on their relative importance. The fifteen top-ranked factors were then used to construct the model and develop the questionnaire. Finally, Structural Equation Modelling (SEM) was utilized to assess the reliability and validity of the constructs. The SEM results confirmed the reliability and validity of all model constructs, including the items. Based on these findings, a validated questionnaire has been formulated for future research. This questionnaire is designed to gather data to test hypotheses and identify statistically significant factors that influence the adoption of blockchain technology in e-government.